Assessing the demand of route network for locating a bus terminus in a city – A case study of gandhipuram bus terminus (Coimbatore city). (2022) - Logeswaran, S.; Anandaraj, S.; Yuvaraj, S.; Karthik raja, K.S.; Jawahar, K.S.; Krishnan, A. Gokula; Nandhika, E.; Ajaynivethan, S.
Abstract: Coimbatore is the second largest city in Tamilnadu. The bus terminus infrastructure in the city is not sufficient to handle the capacity of buses. Therefore, the Tamilnadu government has decided to construct new bus terminus at Vellalore. But when the route network between the existing bus terminus and the location of new bus terminus provides the inconvenient route behaviour for the passengers. This research work executes the route behaviour analysis for locating the efficient and accessible bus terminus inside the skirts of the city. The demand of various routes and the expectations of passengers has been analysed based on the questionnaire survey and the finalised route choice has been predicted based on the demand of the passengers and bus services.